Three Component Reaction: An Efficient Synthesis and Reactions of 3, 4-Dihydropyrimidin-2(1H)-Ones and Thiones Using New Natural Catalyst. (18th August 2013) - Elmaghraby, A. M.; Mousa, I. A.; Harb, A. A.; Mahgoub, M. Y.
Abstract : Synthesis of 3, 4-dihydropyrimidin-2(1 H )-one and 3, 4-dihydropyrimidin-2(1 H )-thione derivatives from aldehydes, 1, 3-dicarbonyl derivatives and urea or thiourea using granite and quartz as new, natural and reusable catalysts. Some of the 3, 4-dihydropyrimidin-2(1 H )-thione derivatives were used to prepare new heterocyclic compounds. The antimicrobial activity of selected examples of the synthesized compounds was tested and showed moderate activity.